AN ANALYSIS OF CONVERSATIONAL IMPLICATURE STRATEGY IN A DRAMA “THE BEAR” BY ANTON CHEKHOVAND ITS APPLICATION IN ELT - Hendra Suryadi; Muslim Muslim (Universitas Pendidikan Mandalika, 2019)
This study was aimed at finding analysis of conversational implicature in a drama “the bear” by Anton Chekhov and its application in English language teaching